2021
DOI: 10.1088/2631-8695/ac3e10
|View full text |Cite
|
Sign up to set email alerts
|

Study on the effect of temperature and strain rate on Ni2FeCrCuAl high entropy alloy: a molecular dynamics study

Abstract: High entropy alloy has offered significant attention in various material science applications, due to its excellent material features. In this investigation, the mechanical characteristics of Ni2FeCrCuAl High Entropy Alloy (HEA) have been examined under variable temperature and strain rates to analyze its influence over the material features of high entropy alloy through Molecular Dynamics (MD) simulation and it is stated that the formation of various point defects and dislocations are the major cause for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…It is also stated that the temperature has a superior impression on the formation of greater shear strain and dislocation when compared to the loading direction and crack, due to the occurrence of more KE among the atoms. The loading direction and existence of the crack also offer the intermediate and lowermost impact on the shear stain formation, owing to the establishment of decrement in the distortion resistance and stress concentration near the discontinuity or crack [36][37][38][39][40][41][42]. Further, it is observed that under greater temperatures and the loading along the normal to the cross-section of the crack offers superior shear strain generation which primes to stimulus the tensile characteristics of FeCr polycrystal.…”
Section: Resultsmentioning
confidence: 99%
“…It is also stated that the temperature has a superior impression on the formation of greater shear strain and dislocation when compared to the loading direction and crack, due to the occurrence of more KE among the atoms. The loading direction and existence of the crack also offer the intermediate and lowermost impact on the shear stain formation, owing to the establishment of decrement in the distortion resistance and stress concentration near the discontinuity or crack [36][37][38][39][40][41][42]. Further, it is observed that under greater temperatures and the loading along the normal to the cross-section of the crack offers superior shear strain generation which primes to stimulus the tensile characteristics of FeCr polycrystal.…”
Section: Resultsmentioning
confidence: 99%
“…For the tensile loading, the strain rate plays an important role in affecting the strength of nanomaterials, including a one-dimensional (1D) nanotube [ 32 , 34 ], 2D sheets [ 35 ], three-dimensional (3D) metals [ 36 , 37 ], and high-entropy alloys [ 38 ]. To gain insight into the coupled effect of the tensile strain rate, loading direction, and temperature on the fracture strength, additional simulations have been performed on Janus WSSe and MoSSe monolayers at different temperatures ranging from 50 to 300 K with different strain rates of 10 8 /s, 5 × 10 8 /s, and 10 9 /s.…”
Section: Resultsmentioning
confidence: 99%
“…But with the addition in grain diameter or size (under AD to CD condition) the detected creep rates drastically decrease, due to the creation of larger resistive performance between the atoms and grain boundaries. From the above analysis, it is measured that the higher grain size with minimal pressure and 2 that the creep environments and grain size have a larger influence on the creep behavior and creep properties, and it is also exposed that the pressure has a more substantial impact on the creep performance, due to changes in the restrictive performance of atoms [28][29][30][31]. Based on the foregoing discussions, it is confirmed that the Mg-1.8Zn-0.3Ca alloy performs best when the lowest applied pressure is combined with the lowest temperature and alloying element.…”
Section: Effect Of Temperature Grain Diameter and Pressure Over The M...mentioning
confidence: 99%